2006
DOI: 10.17221/3547-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quercetine on leaf abscission of apple tree (Malus domestica Borkh.), growth of flax (Linum usitatissimum L.) and pea (Pisum sativum L.), and ethylene production

Abstract: This study compares effects of 2,3,5-triiodobenzoic acid (TIBA) and flavonoid quercetine (Q). In spite of the fact that both these compounds are inhibitors of the polar transport of auxin, a number of experiments demonstrated that their properties are different. If the flax seedlings were decapitated and one cotyledon was removed, the axillary bud of the remaining cotyledon grew up more intensively while TIBA (0.5% applied in the form of a lanolin paste on the remaining cotyledon) induced a correlative reversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…TIBA and IAA bind to distinct but functionally related sites of the efflux transporter, and as a result, the movement of both molecules is inhibited [55,56]. TIBA has previously been shown to stimulate abscission in pea, orange, coleus, and rose [57][58][59][60]. Our physiological results showed that the direct application of TIBA onto the flower AZ in lupine resulted in excessive organ abscission ( Figure 1A).…”
Section: Discussionmentioning
confidence: 65%
“…TIBA and IAA bind to distinct but functionally related sites of the efflux transporter, and as a result, the movement of both molecules is inhibited [55,56]. TIBA has previously been shown to stimulate abscission in pea, orange, coleus, and rose [57][58][59][60]. Our physiological results showed that the direct application of TIBA onto the flower AZ in lupine resulted in excessive organ abscission ( Figure 1A).…”
Section: Discussionmentioning
confidence: 65%
“…Flavonoids reportedly determine the auxin gradient at the cell and tissue levels by influencing auxin catabolism [ 64 ]. In apple, the flavonoid quercetin, which restricts polar auxin transport, significantly inhibits petiole abscission [ 65 ]. Exposing tobacco roots to low concentrations of epicatechin and quercetin can increase the free IAA content, but treatments with high epicatechin and quercetin concentrations have the opposite effect, suggesting high flavonoid contents in tobacco seedlings are not conducive to the basipetal transport of free IAA [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…for Cucumis sativus (Stenlid 1976); for Arabidopsis thaliana with its Xavonoid biosynthetic mutants of the tt transparent testa phenotypic class (Murphy et al 2000;Brown et al 2001;Peer et al 2001). For Malus, an eVect of the Xavonol quercetin on leaf abscission was demonstrated (Finerová et al 2006). Lc-transgenic apple plants have strongly elevated levels of anthocyanins (average 12-fold) and Xavan-3-ols (7 to 134-fold), but not of Xavonols (Li et al 2007).…”
Section: Growth Habitmentioning
confidence: 98%